Moving towards an equitable long-term care network: a multi-objective and multi-period planning approach - Cardoso-Grilo, T.; Oliveira, M. D.; Barbosa-Póvoa, A. P.; Nickel, S. (Omega, 2016)
This study proposes a multi-objective and multi-period mathematical programming model to support planning decisions in the Long-Term Care (LTC) sector. The model provides information to help planning the delivery of institutional LTC services in the medium-term, both in terms of location selection and capacity planning, when it is intended a move towards an equitable provision of care. For this purpose, three equity-related objectives are accounted for equity of access, geographical equity and socioeconomic equity. Cost considerations are also taken into account. The model objective function incorporates multiple objectives which are scaled into a common unit through weights that are built with the Measuring Attractiveness by a Category-Based Evaluation Technique. The applicability of the model is illustrated through the resolution of a case study in the Great Lisbon region in Portugal.